The PROCESS 2018 statement: Updating Consensus Preferred Reporting Of CasE Series in Surgery (PROCESS) guidelines. (December 2018) - ,; Zhu, Hongyi; Alsawadi, Abdulrahman; Noureldin, Ashraf; Rao, Ashwini; Enam, Ather; Thoma, Achilleas; Bashashati, Mohammad; Vasudevan, Baskaran; Beamish, Andrew; Challacombe, Ben; De Wilde, Rudy Leon; et al.
Abstract: Introduction: The PROCESS guidelines were published in 2016 to provide a structure for reporting surgical case series. The PROCESS guidelines have since been widely endorsed by a number of journals. The requirement to report compliance with each item outlined in the PROCESS statement has improved the reporting transparency of case series across a number of surgical specialties. Here, we undertook a new Delphi consensus exercise to update the PROCESS guidelines. Methods: All members of the previous Delphi group were invited to participate. In addition, researchers, editors, and reviewers who have previously published or reviewed case series with the International Journal of Surgery were invited to collaborate. An online questionnaire was sent to participants asking them to rate their agreement with amendments to each of the 29 items. Results: 140 experts were invited to participate, 56 people agreed to participate, and 45 (80%) recipients completed the survey. There was a high level of agreement amongst the expert group, and unanimous consensus was reached in the first round. All except three proposed items were accepted, and the original guidelines were modified accordingly. Conclusion: A modified and improved PROCESS checklist is presented, after a Delphi consensus exercise was completed. Highlights: A Delphi consensus exercise to update the PROCESS guidelines. 56 people agreed to participate, and 45 (80%) recipients completed the survey. There was high agreement amongst the consensus group. The collated responses resulted in a modified and improved PROCESS checklist, presented in this manuscript.